Cold War Geopolitics of Population and Reproduction in Okinawa Under US Military Occupation, 1945–1972. Issue 4 (1st December 2016) - Sawada, Kayo
Abstract : This article explores the Cold War geopolitics of population and reproduction in Okinawa under US military occupation from 1945 to 1972. Okinawa has been hailed as a "reproductive paradise, " owing to having the highest birth rate in Japan. However, its high birth rate reflects the Cold War history of US military occupation or, more specifically, the history of reproduction and the marginalization of the population in Japan. In postwar Okinawa, where the Eugenic Protection Law (EPL) was not implemented, the use of legalized abortion and contraceptive methods was restricted until the reversion to Japanese administration. The US Civil Administration of the Ryukyu Islands (USCAR) put forward emigration as a solution to Okinawa's population pressures and refused to enact the EPL, although the Government of the Ryukyu Islands (GRI) sought to implement the legislation. This article reveals that Cold War geopolitics placed Okinawa between national and international trends of population policy and family planning programs by highlighting the following three points: the GRI's awareness of Okinawa's population problem and enactment of the EPL, USCAR's choice in promoting emigration and "rescission" of the EPL, and a family planning campaign without state initiative in Okinawa under US military occupation.